Steerable Droplet Bouncing for Precise Materials Transportation. Issue 21 (11th September 2019) - Zhao, Zhipeng; Li, Huizeng; Hu, Xiaotian; Li, An; Cai, Zheren; Huang, Zhandong; Su, Meng; Li, Fengyu; Li, Mingzhu; Song, Yanlin
Abstract: Directional transportation of liquid droplets plays a significant role in various processes including anti‐fogging, anti‐icing, and materials transportation. Diverse strategies have been developed to achieve lateral bouncing of impacting droplets. However, due to the complexity of the interactions on the interface between a droplet and the solid, quantitatively manipulating the directional movement of the droplet still remains challenging. Here, it is proposed that the directional transportation of a droplet with precise controllability can be achieved by impacting it on a heterogenously wettable surface. It is found that the droplet lateral momentum correlates with the surface area of a geometric region that depends on the position‐coupling between the droplet maximum spreading and the wettability pattern. The well‐controlled droplet directional movement has generality for different Weber numbers and diverse superhydrophilic patterns. Based on this principle, functional materials are orientated to achieve precise positioning of regents for demand‐on chemical reactions, and micro‐floats are driven with different moving velocities. It offers a promising strategy for accurate droplet manipulation based on patterned wettability, which shows great potential in applications such as functional materials transportation, microfluidics, and energy collection and utilization. Abstract : A strategy is designed to precisely control droplet bouncing behavior on heterogenous wettability surfaces . This is realized by regulating the relative position between the impacting center and the wettability pattern center. Accordingly, functional materials are orientated for chemical reactions, and micro‐floats are driven with different velocities. This discovery shows potential in functional materials transportation and energy collection/utilization.